Divide and Sharing : Navigating Controversial Issues in the Classroom - Gusacov, Eran (Educational Research E-Books Online, Collection 2026., 2025)
In a polarized world, educators face the challenge of addressing controversial issues in the classroom. This book provides an in-depth exploration of the ethical, philosophical, and practical considerations involved in discussing sensitive topics. Drawing on case studies from Israel and Western democracies, the author offers actionable strategies for fostering critical thinking and civic engagement in students. It addresses the complexities of balancing diverse perspectives, navigating potential conflicts, and promoting informed discussions. Essential for educators, parents, and policymakers, this book serves as a vital resource for those seeking to prepare students for active participation in democratic societies across the globe.